Single-Atom Colloidal Nanorobotics Enhanced Stem Cell Therapy for Corneal Injury Repair - Ju, Xiaohui; Javorková, Eliška; Michalička, Jan; Pumera, Martin (American Chemical Society, 2025)
Corneal repair using mesenchymal stem cell therapy faces challenges due to long-term cell survival issues. Here, we design cerium oxide with gold single-atom-based nanorobots (CeSAN-bots) for treating corneal damage in a synergistic combination with stem cells. Powered by glucose, CeSAN-bots exhibit enhanced diffusion and active motion due to the cascade reaction catalyzed by gold and cerium oxide. CeSAN-bots demonstrate a two-fold increase in cellular uptake efficiency into mesenchymal stem cells compared to passive uptake. CeSAN-bots possess intrinsic antioxidant and immunomodulatory properties, promoting corneal regeneration. Validation in a mouse corneal alkali burn model reveals an improvement in corneal clarity restoration when stem cells are incorporated with CeSAN-bots. This work presents a strategy for developing glucose-driven, enzyme-free, single-atom-based ultrasmall nanorobots with promising applications in targeted intracellular delivery in diverse biological environments.

Corneal repair using mesenchymal stem cell therapy faces challenges due to long-term cell survival issues. Here, we design cerium oxide with gold single-atom-based nanorobots (CeSAN-bots) for treating corneal damage in a synergistic combination with stem cells. Powered by glucose, CeSAN-bots exhibit enhanced diffusion and active motion due to the cascade reaction catalyzed by gold and cerium oxide. CeSAN-bots demonstrate a two-fold increase in cellular uptake efficiency into mesenchymal stem cells compared to passive uptake. CeSAN-bots possess intrinsic antioxidant and immunomodulatory properties, promoting corneal regeneration. Validation in a mouse corneal alkali burn model reveals an improvement in corneal clarity restoration when stem cells are incorporated with CeSAN-bots. This work presents a strategy for developing glucose-driven, enzyme-free, single-atom-based ultrasmall nanorobots with promising applications in targeted intracellular delivery in diverse biological environments.
Single-Atom Colloidal Nanorobotics Enhanced Stem Cell Therapy for Corneal Injury Repair
Keywords: single-atom; cerium oxide; nanorobot; glucose; mesenchymal stem cells; cornea; single-atom; cerium oxide; nanorobot; glucose; mesenchymal stem cells; cornea